Strategi Pemasaran Batara Haji Dan Umrah iB Bank Tabungan Negara Syariah Ditinjau Dengan Analisis SOAR - Sakum, Sakum; Ainulyaqin, MH; Achmad, Listian Indriyani; Mamun, Sukron (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the marketing strategy of Batara Hajj and Umrah iB. The type of research conducted by theauthor is field research (field research) with data collection methods using interviews, observation and documentation. While the technical analysis of the data used is a qualitative approach using SOAR analysis. SOAR analysis is used for the startegic planning process that can be usedby the company. The result of this study indicate that after a SOAR analysis wa carried out at Islamic Bank Tabungan Negara Syariah, it was found to be effevtive in marketing Batara Hajj and Umrah iB, but seeing that there are still large opportunitiesopen along with the many competitors with similar product, the need for strong benefits is needed so as to achieve good marketing.